Base de Datos Espacial con la Información Geocronológica de Colombia en PostgreSQL (2023)
The advance in technology has significantly improved the production of knowledge in all areas of work, including geology. The improvement in radiometric dating analytical techniques and access to specialized laboratories has allowed more radiometric dating to be done, triggering a large volume of geochronological information, which also requires progress in the tools to store and process such data.